Quinazoline scaffold as a target for combating microbial resistance: Synthesis and antimicrobial profiling of quinazoline derivatives - Vishwanath Halappanavar; Sangappa Teli; Hanamant B. Sannakki; Dharyappa Teli (Results in Chemistry)
The rise of drug-resistant microbial pathogens necessitates the development of innovative antimicrobial agents. Quinazoline derivatives exhibit promising pharmacological effects and diverse chemical structures. This review focuses on quinazoline derivatives synthesis and antimicrobial activity, highlighting their potential as antimicrobial agents. Synthetic methods include transition metal-mediated reactions, microwave-assisted techniques, and Aza reactions. The review critically evaluates the efficacy of quinazoline derivatives against drug-resistant pathogens and explores avenues for developing quinazoline-based antimicrobials. Recent advances in antimicrobial activity are also discussed. With their natural accomplishments, quinazoline derivatives have the potential to advance the development of novel antibiotics and fill the gap for potent antimicrobial drugs. Medicinal chemistry researchers seeking novel antimicrobial agents will find this evaluation valuable.